Пейзажі рівнинного району дендропарку “Тростянець”: “Букова поляна” - Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The changes in landscapes composition of a glade in dendropark Trostyanets, which have taken place within last 50 years are analyzed in the paper. Ways of restoration of the broken compositions are outlined.